A Rare Presentation of Five Primary Cancers in an 80-year-old Female Patient with Werner Syndrome - Ruchi Yadav; Shakthi Raman; Dosbai Saparov; Vivek Yadav; Avezbakiyev Boris (Disease and Health: Research Developments Vol. 7, 2025)
Werner syndrome (WS) was first described in 1904 by German physician Otto Werner. This is a rare autosomal recessive disorder characterized by premature aging and higher cancer risk. This is one of the few adult-onset syndromes of accelerated aging in which patients generally develop normally until they reach adolescence. The first sign, often recognized retrospectively, is a lack of a growth spurt and a relatively short stature as adults. WS patients are characterized by a defective gene product, WRN, that plays an instrumental role in the genomic stability of DNA structures. It typically manifests in late adolescence or early adulthood, leading to premature aging, age-related disorders like diabetes, and myocardial infarction, and an increased propensity for developing sarcomas, melanoma, and solid tissue cancer. We present a rare case of an 80-year-old female with WS developing five different primary cancers over a decade namely basal cell carcinoma (BCC) of the face, left-sided urothelial carcinoma, right-sided triple-negative breast cancer (TNBC), right-sided invasive colonic adenocarcinoma, and pancreatic intraductal papillary mucinous neoplasm (IPMN). The patient’s family history is significant for early-stage cervical cancer in her daughter and for diabetes and hypertension in her mother and sister. Our case report is unique in presentation it defies the expected life expectancy of the 50s seen in WS, with the patient currently exhibiting a stable clinical course. The development of five distinct malignancies diagnosed over 14 years in an individual well beyond the typical age of death for WS highlights both the intrinsic genetic factors as well as the extrinsic biological environment playing a significant role in survival. This case highlights the need for further research into the mechanisms behind extended lifespan and atypical tumor spectra in such patients, as well as the development of tailored therapeutic strategies, particularly with regard to chemotherapy.